Estimation of country-specific and global prevalence of male circumcision. Issue 1 (December 2016) - Morris, Brian; Wamai, Richard; Henebeng, Esther; Tobian, Aaron; Klausner, Jeffrey; Banerjee, Joya; Hankins, Catherine
Abstract Background Male circumcision (MC) status and genital infection risk are interlinked and MC is now part of HIV prevention programs worldwide. Current MC prevalence is not known for all countries globally. Our aim was to provide estimates for country-specific and global MC prevalence. Methods MC prevalence data were obtained by searches in PubMed, Demographic and Health Surveys, AIDS Indicator Surveys, and Behavioural Surveillance Surveys. Male age was ≥15 years in most surveys. Where no data were available, the population proportion whose religious faith or culture requires MC was used. The total number of circumcised males in each country and territory was calculated using figures for total males from (i) 2015 US Central Intelligence Agency (CIA) data for sex ratio and total population in all 237 countries and territories globally and (ii) 2015 United Nations (UN) figures for males aged 15–64 years. Results The estimated percentage of circumcised males in each country and territory varies considerably. Based on (i) and (ii) above, global MC prevalence was 38.7 % (95 % confidence interval [CI]: 33.4, 43.9) and 36.7 % (95 % CI: 31.4, 42.0). Approximately half of circumcisions were for religious and cultural reasons. For countries lacking data we assumed 99.9 % of Muslims and Jews were circumcised. If actual prevalence in religious groups was lower, then MC prevalence in those countries would be lower. On the other hand, we assumed a minimum prevalence of 0.1 % related to MC for medical reasons. This may be too low, thereby underestimating MC prevalence in some countries. Conclusions The present study provides the most accurate estimate to date of MC prevalence in each country and territory in the world. We estimate that 37–39 % of men globally are circumcised. Considering the health benefits of MC, these data may help guide efforts aimed at the use of voluntary, safe medical MC in disease prevention programs in various countries.